A New Anti‐forensic Scheme—Hiding the Single JPEG Compression Trace for Digital Image. Issue 1 (1st December 2014) - Cao, Yanjun; Gao, Tiegang; Sheng, Guorui; Fan, Li; Gao, Lin
Abstract To prevent image forgeries, a number of forensic techniques for digital image have been developed that can detect an image's origin, trace its processing history, and can also locate the position of tampering. Especially, the statistical footprint left by JPEG compression operation can be a valuable source of information for the forensic analyst, and some image forensic algorithm have been raised based on the image statistics in the DCT domain. Recently, it has been shown that footprints can be removed by adding a suitable anti‐forensic dithering signal to the image in the DCT domain, this results in invalid for some image forensic algorithms. In this paper, a novel anti‐forensic algorithm is proposed, which is capable of concealing the quantization artifacts that left in the single JPEG compressed image. In the scheme, a chaos‐based dither is added to an image's DCT coefficients to remove such artifacts. Effectiveness of both the scheme and the loss of image quality are evaluated through the experiments. The simulation results show that the proposed anti‐forensic scheme can verify the reliability of the JPEG forensic tools.